Центральні органи виконавчої влади як суб'єкти адміністративно-правового регулювання демографічної політики в Україні - Сенченко, Л.В. (Інститут держави і права ім. В.М. Корецького НАН України, 2009)
Рассмотрено административно-правовое регулирование демографической политики в Украине центральными органами исполнительной власти. Проведен анализ их полномочий в данной сфере. Автор выделяет ряд негативных моментов в регулировании демографической политики центральными органами исполнительной власти и формулирует рекомендации для улучшения их деятельности, учитывая опыт иностранных государств. The following article includes an overview of legal regulations related to demographic policy, which is provided by central government authorities and agencies. The analysis of their jurisdiction is provided. The author denotes the negative aspects in legal demographic policy provided by the central government authorities and agencies and formulates the recommendations for refinement of their actions on the basis of the experience of the foreign countries.